The banana weevil Cosmopolites sordidus - International Network for the Improvement of Banana and Plantain (2001)
THE BANANA WEEVIL - COSMOPOLITES SORDIDUS - Biology and life cycle, symptoms, control methods, distribution, chemical control, cultural control, biological control, host plant resistance, and research needs, EL PICUDO NEGRO DEL BANANO - COSMOPOLITES SORDIDUS - Biología y ciclo de vida, Síntomas, métodos de control, distribución, control químico, control cultural, control biológico, resistencia de la planta hospedante, y necesidades de investigación. LE CHARANÇON DU BANANIER - COSMOPOLITES SORDIDUS - Biologie et cycle de vie, symptômes, méthodes de lutte, distribution, lutte chimique, lutte culturale, lutte biologique, résistance de la plante hôte, et recherches futures.